Consumption of antimicrobial manuka honey does not significantly perturb the microbiota in the hind gut of mice - Doug Rosendale; Christine A. Butts; Cloe Erika de Guzman; Ian S. Maddox; Sheridan Martell; Lynn McIntyre; Margot A. Skinner; Hannah Dinnan; Juliet Ansell (PeerJ, 2016)
The aim of this study was to test the hypothesis that consuming manuka honey, which contains antimicrobial methylglyoxal, may affect the gut microbiota. We undertook a mouse feeding study to investigate whether dietary manuka honey supplementation altered microbial numbers and their production of organic acid products from carbohydrate fermentation, which are markers of gut microbiota function. The caecum of C57BL/6 mice fed a diet supplemented with antimicrobial UMF® 20+ manuka honey at 2.2 g/kg animal did not show any significantly changed concentrations of microbial short chain fatty acids as measured by gas chromatography, except for increased formate and lowered succinate organic acid concentrations, compared to mice fed a control diet. There was no change in succinate-producing Bacteroidetes numbers, or honey-utilising Bifidobacteria, nor any other microbes measured by real time quantitative PCR. These results suggest that, despite the antimicrobial activity of the original honey, consumption of manuka honey only mildly affects substrate metabolism by the gut microbiota.